Analisis Efisiensi Teknik Peledakan Top Air Deck Terhadap Fragmentasi dan Digging Time Alat Gali Komatsu PC 2000 pada Pembongkaran Overburden Di Pit Badak PT Multi Harapan Utama, Kalimantan Timur - Josep L. Marpaung; Raimon Kopa (Journals Mining Engineering : Bina Tambang, 2019)
Abstract. Demolition by blasting method is a method commonly used in the mining operations in order to obtain large productivity. Generate rock blasting activities into a certain fragmentation size, so it can be easier to do excavation and transportation. The effectiveness of blasting activities as a benchmark of the success of these explosions which are expected to have appropriate fragmentation and shorten the time of excavation, while the blasting efficiency is a measure of economical blasting activities. This study aims to assess the success of the top air deck blasting technique, and to estimate the optimum length of air decking on Pit Badak, PT Multi Harapan Utama. The research data consisted of powder factor, fragmentation of blasting and digging time excavator unloading. The method research is trial and error as well as statistical modeling. From the analysis conducted for blasting obtained with normal charge the percentage amount of the boulder is 2,29%, digging time 12.73 seconds, and used powder factor of 0.17 kg/bcm. Blasting with top air deck application of techniques derived boulder percentage of 7.59%, digging time 12.33 seconds, and powder factor of 0.14 kg/bcm. The optimum length of the air column (air deck lenght) is 1 meter with the percentage of boulder 7%, digging time 12.30 seconds, with the optimum powder factor 0.1450 kg/bcm. Top air deck techniques has reduce the use of explosives by 10-26%.